Structural analysis and design of industrial building in McDonald Steel Building Products Ltd (MSBPL) - Mobarok, Abdullah (BRAC University, 2018)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2017.